Social Media Advertising And Consumer Behaviour In Chennai City - E. Sheela, E. Sheela; K Kalaiselvi, K Kalaiselvi (Journal of Neonatal Surgery, 2025)
Particularly in metropolitan marketplaces like Chennai, social media advertising has become a potent instrument affecting consumer behaviour. This study investigates how social media platforms affect city dwellers' brand loyalty, product awareness, and purchase decisions. Platforms like Instagram, Facebook, and YouTube have become vital tools for businesses to interact with their target customers as internet penetration and smartphone usage rise. Chennai consumers have a strong propensity for relatable and aesthetically pleasing content, and localised and tailored ads significantly influence their purchasing choices. The survey also emphasises how user-generated content and influencer marketing are becoming more and more important in fostering trust and increasing conversions. This study highlights the revolutionary influence that social media advertising has played in forming Chennai's contemporary marketplace by examining trends and customer response